Single-dose antibiotic prophylaxis in maxillofacial surgery - Hotz, Günter; Novotny-Lenhard, Johanna; Kinzig, Martina; Sörgel, Fritz (Chemotherapy, 1994)
The clinical efficacy of short-term antimicrobial prophylaxis with either one shot of ceftriaxone (1 g) or a course of 3 injections of a fixed combination of mezlocillin (2 g) and oxacillin (1 g) administered over 24 h was studied in a prospective randomized clinical study of 100 patients undergoing elective maxillofacial surgery. Tissue and plasma concentrations of the antibiotics were determined by high-pressure liquid chromatography in 6 tumor surgery patients from each treatment group. Statistical analysis showed the treatment groups to be comparable both demographically and with respect to the types of surgery performed and the durations of the procedures. Only 1 patient in each group developed a postoperative wound infection. It is concluded that 1 g ceftriaxone given 30 min preoperatively meets the pharmacokinetic requirements for perioperative antimicrobial prophylaxis in maxillofacial surgery.
Elektronische Reproduktion der Druck-Ausgabe 11. September 2009
Gesehen am 27.11.2025